The Role of CD56 in Thyroid Fine Needle Aspiration Cytology: A Pilot Study Performed on Liquid Based Cytology. - Tommaso Bizzarro; Maurizio Martini; Carla Marrocco; Donato D'Amato; Emanuela Traini; Celestino Pio Lombardi; Alfredo Pontecorvi; Guido Fadda; Luigi Maria Larocca; Esther Diana Rossi (PLoS ONE, 2015)
BACKGROUND:Fine needle aspiration Cytology (FNAC) fulfills a reliable role in the evaluation of thyroid lesions. Although the majority of nodules are quite easily diagnosed as benign or malignant, 30% of them represent an indeterminate category whereby the application of ancillary techniques (i.e. immunocytochemistry-ICC and molecular testing) has been encouraged. The search for a specific immunomarker of malignancy sheds light on a huge number of ICC stains although none of them attempt to yield 100% conclusive results. Our aim was to define in a pilot study on thyroid FNAC whether CD56 might be a valid marker also in comparison with HBME-1 and Galectin-3. MATERIALS AND METHODS:Inasmuch as this is the largest pilot study using only liquid based cytology (LBC), we selected all the cases only in the categories of benign nodules (BN) and positive for malignancy (PM) for validation purposes. Eighty-five consecutive (including 50 PM and 35 BN) out of 950 thyroid FNACs had surgical follow-up. The ICC panel (HBME-1, Galectin-3 and CD56) was carried out on LBC and histology. RESULTS:All BNs and PMs were histological confirmed. CD56 was negative in 96% of the PM while 68.5% of the BNs showed cytoplasmic positivity for this marker, with an overall high sensitivity (96%) but lower specificity (69%). In specific, our 96% of the PMs did not show any follicular cell with CD56 expression. Different ICC combinations were evaluated showing that the panel made up of CD56 plus HBME-1 and Galectin-3 had the highest sensitivity (98%) and specificity (86%). CONCLUSIONS:Our pilot study suggests that CD56 may be a good marker for ruling out PTC and its variants. The low specificity suggests that an immunopanel including also HBME-1 and Galectin-3 could obtain the highest diagnostic accuracy in thyroid lesions. Our results suggest that CD56 may be a feasible additional marker for identifying malignancies also in the FNs and SMs.